SUBSCAPULARIS TRIGGER RELEASE AND CONTRACT RELAX TECHNIQUE IN PATIENTS WITH SHOULDER IMPINGEMENT SYNDROME - Salameh Bweir Al Dajah; Radhakrishnan Unnikrishnan (European Scientific Journal, ESJ, 2014)
Objectives: The aim of this study is to evaluate the effect of subscapularis trigger release and contract relax technique in minimizing pain, improving glenohumeral external rotation and overhead reach of patients with shoulder impingement. Method: Thirty patients with shoulder impingement syndrome were randomly assigned into two groups; Group (A) and Group (B). Group (A) received subscapularis trigger release and contract relaxes technique to the shoulder, while the control group (B) received range of motion exercise and 0.5 W/cm² Ultrasound to the shoulder. External rotation and overhead reach were taken before and after intervention for both groups. Results: Subjects in group (A) showed a significant reduction in pain with a VAS score of Mean 3.8 Cm, and Group (B) 5.33 Cm with P < 0.283. Shoulder external rotation showed a significant improvement from 36.60º to 52.33º with P < 0.283 among Group A patients. Also, the mean value of overhead reach among Group (A) increased from 163.613 to 172.67 which show significance at P < 0.286. Conclusions: Seven minutes trigger release and 5 repetitions of the contract relax technique to the shoulder internal rotators was found to be effective in reducing pain , gaining glenohumeral external rotation and overhead reach during a single intervention session.